Desenvolvimento de competências digitais na formação continuada de educadores - Lara, Carla Luczyk Torres (2022)
The use of their new development needs and their changing needs in the teaching learning scenario, a context focused on skills building and skills development and on the demand for the development of new practices. This study discusses the development of digital skills of educators in the Municipal Basic Education Network of Tocantins/MG. According to bibliographic research, based on the work of authors considered research references in international and national matrices in the development of competences, a self-assessment tool was applied to determine the level of proficiency in the use and integration of digital technologies by teachers. The range of teaching information. The advances of these contributions are part of the educator's professional trajectory, as well as the understanding of the pedagogical level of self-development, digital culture and teaching. The objective of this research is identified as digital skills linked to the continuing education of teachers in the context of Lifelong Learning. What justifies this investigation is the importance of digital skills, a process that allows the development of formal skills in the use of technology. Years, education development course gradual introduction of digital (DC) in educational courses in recent years, a process that has not developed basic skills for teaching and learning at school and for professionals. The problematizing question seeks answers about the way educators acquired digital skills for the practice of teaching. Theoretical studies define the concepts of Digital Competence, Training and Continuous Learning. The research methodology is qualitative, with a case study and bibliographic data. Tool data is related through self-assessment